NMR spectroscopy using a chiral lanthanide shift reagent to determine the enantiomeric purity of nicotine and the geometric parameters of lanthanide-nicotine complex. - Thuy, Thanh Thi Thu; Duong, Thai Thuy; Khanh, Pham Ngoc; Luong, Dang Vu; Tai, Nguyen Tien (Vietnam Journal of Chemistry, 2012)
In this paper, we reported a simple method for determining the enantiomeric purity of nicotine extracted from tobacco leaves by 13C-NMR spectroscopy using a chiral shift reagent Ytterbium(III) tris[3-(trifluoropropylhydroxy-methylene)-l-camphorate] (Yb(tfc)3). The results showed that the studied native nicotine contained 98% S-Nicotine and 2% R-Nicotine. The geometric parameters of Yb(tfc)3-Nicotine complex were calculated by means of well-known McConnell-Robertson equation.